Macroeconomic analysis of financial distress with productivity as a moderating variable in the banking sector - Sabas Damanik; Holiawati Holiawati; Rachmawati Rachmawati (Jurnalku, 2026)
This study aims to analyze the influence of macroeconomic variables consisting of inflation, interest rates, and economic growth on financial distress in the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period, as well as examine the role of productivity, as a moderation variable. Financial distress is measured using the Altman Z-Score model, while productivity is proxied through the BOPO ratio. The research method used is a quantitative method with panel data regression analysis. The moderation effect test was carried out using the Moderated Regression Analysis (MRA) approach. In this study, the selection of banking samples was carried out using purposive sampling techniques with a sample of 23 companies listed on the Indonesia Stock Exchange as many as 23 banks. The results of this study show that inflation, interest rates, and economic growth together affect financial distress with the support of Signalling Theory. However, only interest rates have an influence on the distress financial variable, supported by Keynesian interest rate theory. Inflation and economic growth, on the other hand, have no effect, as supported by the Classical Neutrality of Money Theory, and Business Cycle Theory. In addition, the results of the moderation test showed that productivity was unable to moderate the relationship between independent variables (inflation, interest rates and economic growth), with financial distress according to Operating Efficiency Theory, which means that high productivity indicates large operational costs so that companies are unable to utilize productivity against distress risk. This set of results has substantial relevance for investors and policymakers.